Analysis Of Differences In Knowledge Before And After Emergency Education And Skills In Members of Public Safety Center (PSC) 119 - Kamesyworo, Kamesyworo; Hartati, Sri; Haryanti, Eka (Journal of Applied Nursing and Health, 2024)
Background: An emergency refers to a life-threatening situation, while an emergency requires immediate intervention to mitigate threats to the victim's life. It represents a critical state that necessitates prompt action to prevent disability or death. An emergency is a clinical condition requiring urgent medical attention to save lives and avoid permanent harm. This study aims to assess whether there is a difference in knowledge regarding the initial management of medical emergency cases among PSC 119 members of the Lahat Regency Health Office before and after receiving health education. Methods: This study used a quasi-experimental design with a one-group pretest-posttest approach. The sample included 16 members of the PSC at the Lahat Regency Health Office. The paired sample t-test analysis of the pretest and posttest results revealed a significant increase in the knowledge of the PSC 119 members regarding the initial management of medical emergency cases after receiving health education. Results: The T-test result showed p=0.00 (<0.05), indicating a significant improvement in knowledge after health education. As for skills, the paired sample t-test results between pre- and post-training showed a substantial increase in skill levels. The T-test result was p=0.000 (<0.05), meaning Ha is accepted, and Ho is rejected. Thus, it can be concluded that health education on emergency management positively influences both the knowledge and skills of PSC 119 members." Conclusion: Health education on emergency management significantly improves the knowledge and skills of PSC 119 members at the Lahat Regency Health Office. Regular training programs are recommended to enhance their emergency response capabilities and ensure better outcomes in critical situations. Future research should evaluate the long-term impact and practical application of such training.